Hubungan Dukungan Sosial Teman Sebaya dengan Penyesuaian Diri Remaja SMA Negeri 8 Surakarta - Anisya Hafsah Subekti; Syafira Putri Kirana; Suparmi Suparmi (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to examine the relationship between peer social support and the adjustment of high school adolescents at SMA Negeri 8 Surakarta. This research employs a quantitative approach with a survey method to collect numerical data that can be statistically analyzed. The sample consists of 125 students from grades X to XII, selected through purposive sampling based on criteria of being active adolescents willing to participate. Data were collected using a Likert-scale questionnaire and analyzed through validity, reliability, normality, and Pearson correlation tests. The results indicate a significant positive relationship between peer social support and adolescent adjustment, with a correlation coefficient of r = 0.553 (p < 0.05), which is categorized as moderate. This finding suggests that adolescents who receive higher levels of peer support tend to adapt better socially, emotionally, and academically. The study highlights the critical role of peers in facilitating adolescent adjustment and offers practical implications for schools, including the development of programs to enhance peer support, social skills training, and counseling interventions to foster psychological well-being and optimal adaptation during adolescence.